2019
DOI: 10.1038/s41598-019-43431-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum amino acid profiles and risk of type 2 diabetes among Japanese adults in the Hitachi Health Study

Abstract: Amino acids have emerged as novel biomarkers for predicting type 2 diabetes (T2D), but the epidemiologic data linking circulating amino acid profiles with T2D are sparse in Asian populations. We conducted a nested case-control study within a cohort of 4,754 nondiabetic Japanese employees who attended a comprehensive health checkup in 2008–2009 and agreed to provide blood samples. During a 5-year follow-up, incident T2D cases were ascertained based on plasma glucose, glycated hemoglobin, and self-report. Two co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 44 publications
5
74
0
Order By: Relevance
“…Besides BCAAs and AAAs, other common amino acids are potential biomarkers, such as glutamine and glutamate, of the dysregulation of carbohydrates metabolism. In recent studies, the profile of amino acids, including BCAAs, AAAs and glutamine and glutamate, has been linked with risk factors related to T2D [28,147]. In this section, plasma glutamine, glutamate and their ratio will be discussed as potential biomarkers for T2D as it is showed in several studies [148].…”
Section: Glutamate Family: Glutamine and Glutamatementioning
confidence: 96%
“…Besides BCAAs and AAAs, other common amino acids are potential biomarkers, such as glutamine and glutamate, of the dysregulation of carbohydrates metabolism. In recent studies, the profile of amino acids, including BCAAs, AAAs and glutamine and glutamate, has been linked with risk factors related to T2D [28,147]. In this section, plasma glutamine, glutamate and their ratio will be discussed as potential biomarkers for T2D as it is showed in several studies [148].…”
Section: Glutamate Family: Glutamine and Glutamatementioning
confidence: 96%
“…AA: Elevated (serum/plasma) AA level is an important early biomarker of glucose intolerance, insulin insensitivity and, subsequently, diabetes. Many epidemiological cohort studies have witnessed an increased level of AA in newly diagnosed diabetic patients in the follow up investigations hinting towards an impaired glucose/hexoses metabolism [14]. An increased serum AA level reduced the insulin sensitivity and uptake of hexoses by offering competition at the substrate level to glucose oxidation and also by interfering with insulin signaling [11,13].…”
Section: Biomarkers Of Disturbed Protein Metabolismmentioning
confidence: 99%
“…Indeed, the association between plasma amino acid levels and the risk of type 2 diabetes has been analyzed in a number of studies. In particular, Chen et al 8 reported that a high glutamine concentration and glutamine-to-glutamate ratio were associated with a decreased risk of the incidence of type 2 diabetes in a nested case-control study in non-diabetic Japanese individuals. As glucagon levels were not analyzed in the study, the association between glutamine concentration and glucagon levels in plasma remains a matter of conjecture.…”
mentioning
confidence: 99%